Coupled oxidative ageing and mechanical multiphysics modelling of asphalt pavements - Zhang, Hanyu (2025)
Predicting the long-term pavement performance is one of the most significant challenges in pavement engineering, as it is closely related to pavement design strategies and maintenance decision-making. Pavement oxidative ageing must be considered in the long-term performance prediction, as it predominantly influences the viscoelastic properties and damaging behaviours of road materials throughout their life cycles. To couple the oxidative ageing into the long-term pavement performance predictions, a Multiphysics finite element (FE) modelling framework is developed in this thesis to fundamentally investigate and model the interplay between pavement ageing and performance prediction.